The correlations between DNA methylation and polymorphisms in the promoter region of the human telomerase reverse transcriptase (hTERT) gene with postoperative recurrence in patients with thyroid carcinoma (TC) - Jian-Jun Li (World Journal of Surgical Oncology, 2017)
Abstract Background This study aims at exploring the correlations between DNA methylation and polymorphisms in the promoter region of the human telomerase reverse transcriptase (hTERT) gene and postoperative recurrence in patients with thyroid carcinoma (TC). Methods A total of 312 patients diagnosed with TC were chosen for the study and categorized into recurrence (n = 75) and non-recurrence (n = 237) groups. The hTERT rs2736100 and rs2736098 polymorphisms were detected by performing polymerase chain reaction-restriction fragment length polymorphism. DNA methylation in the promoter region of hTERT gene was evaluated by pyrosequencing. A telephonic and/or outpatient follow-up was conducted for all patients. The correlations of DNA methylation and polymorphisms in the promoter region of hTERT with postoperative recurrence of TC patients underwent analysis. Results The patient in the recurrence group showed evidently different pathological types and tumor stages in comparison to the non-recurrence group. The GG genotype of hTERT rs2736100 might increase the recurrence risk of TC patients. No correlations between hTERT rs2736098 polymorphisms and recurrence risk were observed. Compared to the TT + TG genotype frequency, the rs2736100 GG genotype frequency increased in patients without multicentricity, patients with extrathyroidal invasion, patients with lymph node metastasis, patients with undifferentiated carcinoma, and patients in the III + IV stage. The recurrence group showed significantly higher DNA methylation level compared to the non-recurrence group. The DNA methylation level was closely associated to tumor stage and lymph node metastasis of TC patients in the recurrence group. Conclusions The DNA methylation and rs2736100 polymorphisms in the promoter region of hTERT gene might be in correlation to postoperative recurrence of TC patients.